Virtual Reality, Augmented Reality and beyond: Laboratory of Computer Applications for Health Care at University of São Paulo - Nunes, Fátima; Aranha, Renan; Testa, Rafael; Ribeiro, Matheus (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
The Laboratory of Computer Applications for Health Care at University of São Paulo develop multidisciplinary research involving Computer Science areas and other knowledge fields such as Physiotherapy, Psychiatry, Radiology, and Cardiology. Most studies use concepts besides Computer Science, by aggregating knowledge to solve real problems. In this paper we present the main projects in Virtual Reality and Augmented Reality areas, highlighting serious games, computer-aided diagnosis and therapy, simulation and training. Besides the social and scientific impact inherent to the type of the developed research, some systems are available to health professionals in order to allow technology transfer and consequent technological and economic impact in daily activities of health tasks.